The Implementation of Electronic Contract on Business to Business (B2B) Electronic Transaction - Wiraguna, Sidi Ahyar; Santiago, Faisal (International Journal Labs, 2022)
Background: Before technology was widely used, transactions were carried out directly or non-electronically so that contracts in transactions were made in physical form. Due to the rapid development of the times, non-electronic transactions are now with a touch of technology turning into electronic transactions considering the many conveniences and cheapnesses obtained. As with direct transactions, sometimes in running a business, a contract agreement is needed. Aim: This study analyzed the implementation of electronic contract on B2B electronic transaction. Method: This study uses a normative legal research method with a normative juridical approach, while data collection techniques are carried out by exploring journals, books and applicable laws and regulations. The data obtained were then analyzed qualitatively and presented descriptively. Findings: The results of the study show that the implementation of electronic contracts in electronic transactions is based on the need to make long distance agreements while still fulfilling the legal requirements of the agreement including agreements, people who are adults and there are no obstacles to carrying out legal actions, certain rights and legal causes. So it can be concluded that the electronic contract is similar to a conventional contract, the only difference being that the electronic contract is created through an electronic system process while the conventional contract is created not through an electronic system process but is directly created orally or in writing on a special paper.